GSM 900 MHz microwave radiation affects embryo development of Japanese quails - Tsybulin, Alexander; Sidorik, Evgeniy; Kyrylenko, Sergey; Henschel, Denis; Yakymenko, Igor (My University, 2012)
The irradiation led to a signiﬁcant increase in numbers of differentiated somites in 38-hour exposed embryos and to a signiﬁcant increase in total survival of embryos from exposed eggs after 14 days exposure. A level of thiobarbituric acid (TBA) reactive substances was signiﬁcantly higher in brains and livers of hatchlings fromexposed embryos.
Keywords: electromagnetic radiation; embryogenesis; peroxidation; електромагнітне випромінювання; ембріогенез; перекисне окиснення; электромагнитное излучение; эмбриогенез; перекисное окисление; кафедра екології та екоменеджменту